In vivo production of three entomonematodes with two infection systems in two hosts - MOLINA-ACEVEDO, JUAN PABLO; LÓPEZ-NÚÑEZ, JUAN CARLOS (Revista Colombiana de Entomología, 2001)
The use of entomonematodes (EN) as a biological control, is a very valuable tool within an Integrated Pest Management program. The mass production in laboratory is a limiting factor and is necessary to develop studies about behavior, pathogenicity and biological activity on insect pest populations in laboratory, needed to seek an easy and economic alternatives of in vivo mass production. This paper describes an in vivo production technique of three EN EN (Rhabditida: Steinernematidae) Steinernema carpocapsae Brasil, Steinernema carpocapsae Ali strain, and Steinernema cubanum, in two insect host: Gallería mellonella (Lepidoptera: Pyralidae) and Bombyx morí (Lepidoptera: Bombycidae) and two infection systems: topical and injection, to standardize parameters of production and to realize pathogenicity proofs. A randomized experimental design in a factorial arrangement 3x2x2, 12 treatments each one composed by ten larvae was evaluated. Daily and accumulative production of EN stages (JI, J4, males and females/larvae) and host production percent were observed every 24 hours, from EN emergency to depletion host. The treatments S. carpocapsae Brasil by the topical system in G. mellonella and S.carpocapsae All strain by injection system in B. mori,  presented the highest accumulative production 149.258 Jl/larvae and 139.756 Jl/larvae respectively. lt also did obtain the highest production for S. carpocapsae Ali strain in B. morí by injection system (139.880 JI). S. cubanum was not reproduced under any infection system in B. morí, but in G. mellonella, being a specific host. G. mellonella by topical system and B. morí by injection system, registered the highest level of production of JI between third to fifth day after infection time to harvest the EPN production. G. mellonella is ratified as the most effective host to reproduce EN, however B. morí can be used as an alternative of production in vivo of EN.